Akurasi Model Trait Recognition (TR) sebagai Model Prediksi Kebangkrutan Bank di Indonesia - Riskia Zuliannisa (Universitas Darwan Ali, 2021)
The banks that are often liquidated every year are the People's Credit Bank (BPR), while we rarely find commercial banks going bankrupt. In order for the company to continue operating, it is necessary for managers to always re-analyze, especially financial ratios. There are only 2 previous researchers who were correct and accurate in predicting bank bankruptcy. However, this research was conducted 17 years ago in connection with the 1998 monetary crisis and of course, the conditions are different now. This study uses the Trait Recognition (TR) model to determine the accuracy in predicting bankruptcy with a sample of 20 bankrupt banks and 20 non-bankrupt banks in the 2013-2017 period and using a purposive sampling method. The results show that the TR model has anaccuracy rate below the 80% standard accuracy. This study does not support previous research conducted because of the newness of the studied bank, a research phenomenon that is motivated by the economic conditions of each country, different study periods, as well as when the last study was conducted 17 years ago.